ESP OPTIMIZATION IN AN INTEGRATED WELL PRODUCTION SYSTEM - PARULIAN SIMBOLON (NIM : 22208019), FERNANDO
Electric Submersible Pump (ESP) is one of the artificial lift method that can give an additional pressure to the fluid reservoir to help it to flow into the surface through the tubing up to the separator on the amount of ESP production capacity, where the ESP performance is influenced by the amount of flow rate that can be given by the reservoir. Wells that is produced by using the ESP will certainly having a decrease in its productivity, this condition is allowing the ESP to operate outside its specification and may result in damage (downthrust). Replacement of the ESP which requires work over operations is needed to avoid such condition that requires a high cost. Thus ESP that able to operate in a relative long time is required. Determination of ESP with these criteria is carried out in an integrated system of production wells. The objective of this thesis is to choose a type of ESP that operates in constant production rate at a relative long time interval in accordance with reservoir capacity. The selection of ESP is based on the current speed of the production rate through the annulus of casing and motor in the amount of 1ft/second. This research is conducted by developing model that consists of all components in oil field production system. The integrated model represented by ECLIPSE Simulator (reservoir), PIPESIM Simulator (production well and flowline network) and the interface FPT (Field Planning Tools) of ECLIPSE and PIPESIM. Using this integrated model the ESP operating time with a constant production rate can be determined. Determination of the ESP with a long range operation time will be done on several scenarios, that is for the casing 5, 6, and 7 inch, and by doing variations of the depth position of ESP. The simulation results show that ESP operates at a constant production rate with the longest operation time on the initial reservoir condition is DN675 that is operate for 707 days in 5 inch casing, D950 that is operate for 364 day in 6 inch casing, and DN1750 that is operate for 126 days in 7 inch casing. Work over scheduling is performed using the ESP specification that has been mentioned, and the result is work over is only happens once in third scenario.